The use of code-switching at the 12th grade bahasa program class IN MA Mafatihul Huda - Heru Priyatna; susilawati susilawati (Concept : Community Concern for English Pedagogy and Teaching, 2018)
This research is aimed at insvetigated; (a)The types of code-switching commonly used by the English teacher and students in class Bahasa. (b)The factors triggering the English teacher and students to use code-switching in class Bahasa. (c)The functions of code-switching used by the English teacher in class Bahasa. This research was conducted through descriptive qualitative method. The samples of the research consisted of one English teacher and students at MA Mafatihul Huda. In order to gather the data, this study used two instruments of research, they were: observation note, and interview. The types of code-switching appearing in the classroom were observed based on the theory proposed by Poplack, while the factors triggering the teachers to use code-switching in the classroom proposed by Holmes, and the functions of code-switching in the classroom were perceived through the functions proposed by Sert. The findings indicate that the types of code-switching are simply find in three types: (a) inter-sentential switching (without inserting new information and which inserts new information), (b) intra-sentential switching, and (c) ekstra-sentential (tagswitching). The factors triggering the English teachers to use code-switching in the classroom is find for four reasons, they are: (a) rhetoric reason, (b) differences of status and formalities, (c) quote other statements or proverbs, and (d) lack of vocabulary. And another factors gather from the classroom setting are: (a) the student’s ability in English are not the same, (b) code-switching emerges automatically or unconsciously, and (c) helping the students to share their ideas. Moreover, the functions of code-switching used by English teachers in the classroom are find for three functions; (a) topic switch, (b) affective function, and (c) repetitive function. Keywords: Code Switching